Analysis of Students' Thinking Errors in Solving HOTS-Based Mathematics Problems at SMP Negeri 1 Kedungwaru Tulungagung - Winarko, Adji; Setyani, Rahyu; Eva Trisnantari, Hikmah (Lafadz Jaya Publisher, 2025)
Higher Order Thinking Skills (HOTS) are essential competencies in mathematics learning to face the challenges of the 21st century. However, junior high school students often experience difficulties in solving HOTS problems, indicating the presence of systematic thinking errors. These errors, if not explained in depth, can hinder students' cognitive development and problem-solving abilities. This study aims to analyze the types of thinking errors made by students in solving HOTS-based mathematics problems using the Newman Error Analysis approach. This study uses a qualitative descriptive approach. The subjects consisted of 10 seventh-grade students of SMP Negeri 1 Kedungwaru, classified based on their ability levels (high, medium, and low). Data collection techniques included administering HOTS questions, think-alouds, and semi-structured interviews. Data were analyzed based on Newman's five error categories: reading, understanding, transformation, process skills, and answer writing. The results showed that students' thinking errors in solving HOTS math problems were caused by various factors. Reading errors arose from unfamiliarity with mathematical terms, misunderstanding of problem sentences, confusing question length, and low analytical skills. Comprehension errors were caused by the inability to identify information and difficulty formulating data into mathematical sentences. Transformation errors occurred due to the inability to translate information into mathematical form and a lack of experience working on contextual problems. Process skill errors were influenced by weak arithmetic skills and unfamiliarity with following procedures for solving story problems. Meanwhile, answer writing errors were caused by inaccuracy, weak arithmetic skills, and unfamiliarity with writing final conclusions.